2016
DOI: 10.1080/10410236.2016.1214221
|View full text |Cite
|
Sign up to set email alerts
|

“You Know the Medicine, I Know My Kid”: How Parents Advocate for Their Children Living With Complex Chronic Conditions

Abstract: Caring for a child with a chronic condition has received considerable attention in the pediatric health literature. Today, approximately 1 out of 5 North American children are diagnosed with a chronic condition that requires parents to become caregivers and advocates. Although advocacy is regarded as a significant aspect to parental caregiving, more research is needed to better define this oversimplified and misrepresented concept in clinical practice and research. Subsequently, we interviewed 35 parents of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…The multidimensional care required to manage multiple condition-related needs [12,15,19,23,25,35,42,44,46,51,61,76,82,86,96,99,107,122,123,125,128,131,133,145,150], in the context of developmental, social, and psychological needs, emerged as a key feature of children's CCNs [46,54,61,63,71,149]. Heterogeneous combinations of high-intensity needs [25,33,40,42,45,51,54,76,79,96,98,99,103,128,131,145] spanned a wide range of care, including nutritional [1,10,11,21,25,32,69,76,…”
Section: Heterogeneous and Substantialmentioning
confidence: 99%
See 2 more Smart Citations
“…The multidimensional care required to manage multiple condition-related needs [12,15,19,23,25,35,42,44,46,51,61,76,82,86,96,99,107,122,123,125,128,131,133,145,150], in the context of developmental, social, and psychological needs, emerged as a key feature of children's CCNs [46,54,61,63,71,149]. Heterogeneous combinations of high-intensity needs [25,33,40,42,45,51,54,76,79,96,98,99,103,128,131,145] spanned a wide range of care, including nutritional [1,10,11,21,25,32,69,76,…”
Section: Heterogeneous and Substantialmentioning
confidence: 99%
“…Nonetheless, it was apparent from the medical [1,2,10,40,45,48,51,54,56,66,73,79,89,103,115] and nursing literature [3,4,21,43,68,69,80,93,121,143] that those advances had also led to a growing pediatric population living with secondary conditions and/or disabilities with CCNs. Further, there was strong cross-disciplinary consensus that social and community service developments had not kept pace with medical progress [19,54,60,69,96,99,107,131,137,143]. This shortfall included training and workforce development for healthcare professionals whose job descriptions had rapidly evolved in a climate of advancement and cost containment [4,8,17,46,61,95,149].…”
Section: Medical Advancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Empowering Others-Finally, empowered parents may work to empower others [25,37,38]. Specifically, one study reported empowered mothers sharing their experiences in hopes of empowering other mothers in similar situations [39].…”
Section: 26mentioning
confidence: 99%
“…Engaging parents in the care process not only improves transparency, but having an active role also increases feeling of being in control. This positive effect of engagement, by parents’ advocacy, is also mentioned by the review of Rafferty and Sullivan (Rafferty & Sullivan, ). The factors found to cause insecurities go beyond the seven triggers of that heighten parental uncertainty in chronic, life‐threatening childhood illness of Cohen (Cohen, ).…”
Section: Discussionmentioning
confidence: 53%